Language Learning: Reading Comprehension, Motivation, Strategies, And Academic Achievement - Parmis, Annie A.; Bandalan, Rose B.; Clerigo, Jade C. (Archives of Business Research, 2020)
This study was focused on language learning in terms of reading motivation and comprehension as well as with language learning strategies in relation to academic achievement of college students at the Visayas State University (VSU). The first set of respondents composed of forty-eight (48) Bachelor of Arts in English Language (AB-EL) students took a reading comprehension test and answered a reading motivation survey adopted from Wigfield and Guthrie (1997). The second set of respondents composed of thirty-one (31) Spch 11 (Speech Communication) students answered a survey on language learning strategies adopted from Oxford (1990). The study followed a descriptive survey design. Data were analyzed using descriptive statistics. Spearman’s Rho was also used for correlation analyses. With regard to the reading motivation and comprehension of the AB-EL students, results showed that among the 11 aspects of the Motivation for Reading Questionnaire (MRQ), three of them emerged as having a significant relationship with reading comprehension. These are "challenge", "compliance" and "reading work avoidance". "Challenge" is positively correlated while "Compliance" and "Reading Work Avoidance" are negatively correlated to reading comprehension. This result implies that those who feel challenged while engaging in the reading selection have a higher level of reading comprehension. However, those who read because they are required to do so have a lower reading comprehension than those who read because they choose to do so. Also, those who tend to read to escape from work have a lower level of reading comprehension. Therefore, one’s reading motivation can in a way affect his or her reading comprehension. Among the three factors that have a significant relationship with reading comprehension, "Compliance" is considered to be the most influential to students’ reading comprehension. Therefore, reading to accomplish a requirement has a greater negative effect on the students’ reading comprehension than reading to have an excuse to escape from work. It is disadvantageous because reading for the sake of completing or accomplishing a requirement or task is not the ideal expectation when someone reads for comprehension. Reading for comprehension embodies everything from meaning-making to experiential learning. Meanwhile, with regard to the language learning strategies in relation to the academic achievement of Spch 11 students, findings revealed that only Affective Strategies correlate with the students’ academic achievement ("good" to "very good"). This implies that all the other language learning strategies covering Memory, Cognitive, Compensation, Metacognitive, and Social are independent to the respondents’ academic achievement. Therefore, this study concludes that the affective factors have something to do with one’s language learning strategy. Affective strategies tend to have a powerful influence on the techniques to help students control their emotions, attitude, motivation, and values, thus facilitating one’s language learning.